Upaya Perlindungan Hukum Terhadap Anak Sebagai Korban Tindak Pidana Persetubuhan - Hendrawan Hendrawan; Wahyudi Wahyudi; Husain Husain (An-Nisa: Journal of Islamic Family Law, 2025)
In the legal system and child protection in Indonesia, legal protection efforts for children victims of sexual intercourse crimes are very important. The victim's child suffered such great physical, psychological, and social losses that it required a comprehensive and sustainable protection system. This paper examines the various forms of legal protection provided to child victims of sexual intercourse based on applicable laws and regulations and their application in the field. By examining Law Number 35 of 2014 concerning Child Protection, the Criminal Code (KUHP), and Law Number 17 of 2016 as the second amendment to the Child Protection Law which regulates criminal threats for perpetrators of sexual violence against minors, the author uses a normative juridical method. Various challenges, including weak law enforcement, lack of institutional coordination, and lack of victim recovery facilities, have led to legal protection for child victims not being fully ideal, according to the study. Although there has been a law in accordance with the rights of child victims, implementation in the field is still constrained by cultural and institutional barriers. Therefore, it is important to improve the capabilities of law enforcement officials, encourage institutional synergy, and adopt trauma-based healing strategies in the justice system. Effective legal protection guarantees the recovery and future of the victim's child in a holistic and dignified manner, not only by punishing the perpetrator but also by.